Differential effects of extracellular vesicles secreted by mesenchymal stem cells from different sources on glioblastoma cells. (April 2015) - Del Fattore, Andrea; Luciano, Rosa; Saracino, Rossana; Battafarano, Giulia; Rizzo, Cristiano; Pascucci, Luisa; Alessandri, Giulio; Pessina, Augusto; Perrotta, Antonio; Fierabracci, Alessandra; Muraca, Maurizio
<x xml:space="preserve">Abstract</x> Background: Malignant glial tumors, including glioblastoma multiforme, account for 15 – 20% of pediatric CNS malignancies. They are most resistant to therapy and are associated with a poor prognosis. Objective: Given the ability of mesenchymal stem cells (MSCs) to affect glioma growth, we investigated the effects of extracellular vesicles (EVs) derived from MSCs on U87MG glioblastoma cells line. Methods: EVs were isolated from culture media of MSCs from different sources, including bone marrow (BM), umbilical cord (UC) and adipose tissue (AT) and added to U87MG culture. The internalization and the effects of BM-, UC- and AT-MSC-EVs on proliferation and apoptosis of tumor cells were evaluated. Results: Both confocal microscopy and FACS analysis showed internalization of EVs into tumor cells. BM- and UC-MSC-EVs decreased cell proliferation, while an opposite effect was observed with AT-MSC-EVs. Moreover, both BM- and UC-MSC-EVs induced apoptosis of glioblastoma cells, while AT-MSC-EVs had no effect. Loading UC-MSC-EVs with Vincristine further increased cytotoxicity when compared both to the free drug and to untreated EVs. Conclusions: Different effects of MSC-EVs on cancer cells were observed depending on their tissue of origin. Moreover, MSC-EVs can deliver antiblastic drugs to glioblastoma cells.